2007
DOI: 10.3748/wjg.v13.i26.3614
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat and insulin resistance as predictors of non-alcoholic steatohepatitis

Abstract: A m m a r i n T h a k k i n s t i a n , Clinical Epidermiology unit, Ramathibodi Hospital, Mahidol University, Thailand Naruemon Wisedopas, Abstract AIM: To examine whether visceral fat is associated with non-alcoholic steatohepatitis (NASH), to assess for parameters associated with visceral adiposity and to investigate for factors associated with fibrotic severity in NASH. METHODS:Thirty NASH and 30 control subjects u n d e r w e n t b i o c h e m i c a l t e s t s , a n t h r o p o m e t r i c assessment, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
3
34
1
Order By: Relevance
“…It is also closely linked to non-alcoholic hepatic steatosis and CV diseases (9)(10)(11)(12). Here, a novel association between truncal obesity and fetuin A concentrations is demonstrated in the HD population, many of whom are prone to be thinner and have lower BMI.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is also closely linked to non-alcoholic hepatic steatosis and CV diseases (9)(10)(11)(12). Here, a novel association between truncal obesity and fetuin A concentrations is demonstrated in the HD population, many of whom are prone to be thinner and have lower BMI.…”
Section: Discussionmentioning
confidence: 74%
“…It is closely related to non-alcoholic hepatic steatosis, epicardial fat deposition, and insulin resistance (IR), and predicts the occurrence of type 2 diabetes mellitus (DM) in the general population (9)(10)(11)(12). Furthermore, deranged visceral adiposity consequently leads to inflammation, dyslipidemia (13), and higher CV mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced obesity was stated as a risk factor for the development of liver fibrosis by Sobhonslidsuk et al [11] , Ong et al [12] and Ratziu et al [13] . Recent studies revealed that the people with normal body weight but high visceral fat ratio (central obesity) could have NAFLD, metabolic syndrome and insulin resistance [2,3] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the people with normal body weight but high visceral fat ratio (central obesity) could have NAFLD, metabolic syndrome and insulin resistance [2,3] . Sobhonslidsuk et al [11] and Cheung et al [14] stated that abdominal obesity correlated only with liver inflammation and so waist circumference predicts metabolic risk condition with the most significance. Angelico et al [15] and Marchesini et al [16] found a correlation between various degrees of liver steatosis and BMI but we did not detect any relationship between steatosis and BMI ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation